Feline leptospiral infection : with particular emphasis on Leptospira interrogans servor ballum : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Veterinary Pathology and Public Health at Massey University - Shophet, Rashel (Massey University, 1979)
Following a review of the literature this thesis attempts to study the susceptibility of the cat to different leptospiral serovars. Particular studies were conducted to investigate the pathogenicity, development of the carrier state and the serological response of the cat infected by the oral and intraperitoneal route with Leptospira interrogans serotype balluw. To investigate the hazard of the cat as a carrier and to simulate the field situation of prey-predator chain as a likely source of infection cats were fed infected mice. A serological survey was also conducted to determine the most commonly occurring leptospiral infection in the cat.
Keywords: Leptospirosis in cats; Leptospirosis in animals; Leptospira interrogans; Cat diseases